2016
DOI: 10.1177/2050312116676033
|View full text |Cite
|
Sign up to set email alerts
|

Care practices of older people with dementia in the surgical ward: A questionnaire survey

Abstract: Objectives:The objective of this study was to describe the care practices of nursing staff caring older people with dementia in a surgical ward.Methods:The data were collected from nursing staff (n = 191) working in surgical wards in one district area in Finland during October to November 2015. Data were collected using a structured questionnaire and analyzed statistically. The instrument consists of a total number of 141 items and four dimensions. The dimensions were as follows: background information (12 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 20 publications
1
23
1
Order By: Relevance
“…Dementia care was perceived by nurses as consuming additional resources such as time and staff when these resources were already scarce in acute medical units. Other studies have also found that inadequate staffing and heavy workload in hospital led to poor quality of care for clients living with dementia ( Byers & France, 2008 ; Hynninen et al., 2016 ). Nurses in the current study also felt that acute medical environments did not provide enough stimulation for older adults with dementia in terms of therapeutic activities and human interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dementia care was perceived by nurses as consuming additional resources such as time and staff when these resources were already scarce in acute medical units. Other studies have also found that inadequate staffing and heavy workload in hospital led to poor quality of care for clients living with dementia ( Byers & France, 2008 ; Hynninen et al., 2016 ). Nurses in the current study also felt that acute medical environments did not provide enough stimulation for older adults with dementia in terms of therapeutic activities and human interaction.…”
Section: Discussionmentioning
confidence: 99%
“…When older adults with dementia receive care in hospital, 75% of this population will experience responsive behaviors at least once ( Sampson et al., 2014 ). The hospital environment may trigger responsive behaviors among older adults with dementia ( Sampson et al., 2014 ) and lead to feelings of distress, insecurity, anxiety, and fear ( Baille, Cox, & Merritt, 2012 ; Hynninen, Saarnio, & Elo, 2016 ). Hospitalization heightens the sensitivity of clients with dementia to responsive behaviors due to being in an environment with numerous triggers (e.g., noise and poor lighting) and receiving care from staff who have limited knowledge of their preferences ( Schindel Martin et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over half a million Canadians are affected by dementia ( Alzheimer’s Society of Canada, 2016 ). Approximately 25% of hospital beds are occupied by older people with dementia seeking care for acute illnesses ( Hynninen et al., 2016 ). Compared to the general population, people with dementia in hospitals experience poorer nutrition and function, higher risk of death and delirium, and increased risk of falls related to responsive behaviours ( Mukadam & Sampson, 2010 ; Sampson et al., 2009 , 2014 ; Zhu et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…These behaviours are present in response to pain, fear, hunger, or thirst. The hospital environment may trigger responsive behaviours for people with dementia due to an unfamiliar environment ( Sampson et al., 2014 ) and cause feelings of distress, insecurity, anxiety, and fear ( Hynninen et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation